Risk factors for intradomiciliary infestation by the Chagas disease vector Triatoma dimidiatain Jutiapa, Guatemala Factores de riesgo para la infestación intradomiciliaria por el vector de la enfermedad de Chagas, Triatoma dimidiata, en Jutiapa, Guatemala - Dulce Maria Bustamante; Carlota Monroy; Sandy Pineda; Antonieta Rodas; Xochitl Castro; Virgilio Ayala; Javier Quiñónes; Bárbara Moguel; Ranferi Trampe (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Seventeen variables were evaluated as possible risk factors for the intradomiciliary infestation with Triatoma dimidiata in 644 houses in Jutiapa, Guatemala. During 2004 the houses were assessed for vector presence and evaluated for hygiene, cluttering, material comfort, construction conditions and number of inhabitants, among other factors. Chi-square analysis detected significant associations between vector presence and eight variables related to domestic sanitary and construction conditions. Log-linear models showed that regardless of the age of the house, the odds of vector presence were 4.3 and 10 times lower in houses with a good socioeconomic status compared with poor and very poor houses respectively. Log-linear models also pointed to a greater chance of vector presence when walls lacked plastering (3.85 times) or walls had low quality-incomplete plastering (4.56 times), compared with walls that were completely plastered. Control strategies against T. dimidiata should include the introduction of better-quality but inexpensive plastering formulations and better sanitation practices should also be promoted among the population. Such control strategies should not only reduce or eliminate infestation, but also prevent vector reinfestation. Seiscientas cuarenta y cuatro casas en Jutiapa, Guatemala fueron encuestadas en el año 2004 para buscar el vector de la enfermedad de Chagas Triatoma dimidiata. Diecisiete variables relacionadas con las condiciones estructurales y de higiene de las casas fueron registradas y evaluadas como factores de riesgo para la infestación intradomiciliar con T. dimidiata. Análisis chi-cuadrado detectaron asociaciones significativas entre la presencia del vector y 8 de estas variables. En modelos log-lineares se detectó, que sin importar la antigüedad de la casa, las posibilidades de presencia del vector fueron 4,3 y 10 veces más bajas en casas con un buen estado socioeconómico que en casas pobres o muy pobres, respectivamente. Además, las posibilidades de infestación fueron mayores en casas con paredes sin repello (3,85 veces) o con repellado incompleto o de mala calidad (4,56 veces), que con repellado completo. Las estrategias para el control de T. dimidiata deberían incluir la introducción de repellos baratos y de buena calidad y la promoción de mejores prácticas sanitarias. Estas estrategias no solo reducirían o eliminaría la infestación, sino también ayudaría a prevenir la reinfestación.